The phenomenon of déjà vu in focal epilepsy, literature review - M. Yu. Kissin; T. M. Goguadze; Yu. A. Yakovleva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Introduction: The paper examines the features of the phenomenon of déjà vu in focal epilepsy. The article presents the main anatomical, clinical and psychopathological features of this phenomenon. Material and methods: the analysis of Russian and English-language articles in scientific databases from 1905 to 2022 was carried out. The selection of scientific primary sources for analysis was carried out in the Russian eLibrary, the English PubMed, as well as in open sources. The following search queries were generated for the search: «deja vu phenomenon», «deja vu in epilepsy», «phenomenon of what has already been seen». To search in the English-language database, the queries are formed: «deja vu experience», «deja vu in epilepsy», «deja vu in neurology». A total of 112 sources were studied, in the final analysis remained 39 sources (34%). Results:various brain formations take part in the development of déjà vu in epilepsy, among which the medial sections of the right temporal region, the structures of the limbic system. The connection of the phenomenon of «already seen» with affective disorders is emphasized. The data on the characteristic signs of «already seen» in focal epilepsy are presented, namely, their paroxysmal nature, the presence of a focus of epileptiform activity on the EEG, its localization, lateralization. Conclusion: to date, déjà vu in epilepsy is not sufficiently covered in Russian and foreign sources. Research is mainly devoted to the anatomical, pathophysiological features of this phenomenon. There are no basic psychopathological characteristics of déjà vu in epilepsy, data on prognostic significance.